Isotope dependence of beta-induced Alfvén eigenmode (BAE) and low frequency mode (LFM) stability in DIII-D. (21st September 2021) - Heidbrink, W.W.; Choi, G.J.; Van Zeeland, M.A.; Austin, M.E.; Degrandchamp, G.H.; Spong, D.A.; Bierwage, A.; Crocker, N.A.; Du, X.D.; Lauber, P.; Lin, Z.; McKee, G.R.
Abstract: The stability of beta-induced Alfvén eigenmodes (BAE) and the low frequency modes (LFMs) that were formerly called beta-induced Alfvén-acoustic eigenmodes is discussed. After a brief summary of previous publications on the stability in DIII-D beam-heated, reversed-shear, deuterium plasmas with deuterium neutral beam injection (NBI), new observations in mixed hydrogen and deuterium plasmas are reported. With deuterium NBI, BAEs are at least as unstable in mixed-species plasmas as in deuterium plasmas; however, with hydrogen NBI, the BAEs are stable. In contrast, the LFMs are unaffected by changes in beam species, consistent with the previous observation that LFMs are not driven by high-energy beam ions. As predicted by theory, the LFMs appear more unstable in mixed species plasmas than in pure deuterium discharges.